Breastfeeding self-efficacy and related factors during early postpartum period - Topuz, Şenay; DUMAN, Nuriye BÜYÜKKAYACI; UYSAL, Gulzade; Öcalan, Dilek (Faculty of Medicine, Universitas Trisakti, 2021)
BACKGROUNDBreastfeeding self-efficacy (BSE) could be an indicator of the performance of mothers in breastfeeding during the immediate postpartum time period. The factor most affecting the duration and success of breastfeeding is the self-efficacy perception of the mothers. This study was carried out to determine the BSE and the factors related to it in the early postpartum period. METHODSA cross-sectional study was performed involving 264 mothers. Data were collected by using a questionnaire and the BSE scale (BSES). The questionnaire consisted of questions regarding descriptive characteristics (age, educational status, family type, income level, etc.) and obstetric characteristics regarding pregnancy, delivery and breastfeeding status (number of pregnancies, number of births, type of delivery, planned and desired pregnancy, birth weight, first breast-feeding time after birth, etc.). Simple and multiple linear regression were performed to examine factors related to BSE. RESULTSThe mean BSE score of the mothers participating in the study was 65.20 ± 9.3. Simple and multiple linear regression models indicated that significant determinants of BSE score include having nuclear family type, having social security, a greater number of pregnancies, a greater number of births, the status of antenatal visits in pregnancy, the status of getting information about breastfeeding, and short first breastfeeding time. Getting information about breastfeeding was the most influential factor of BSE (Beta=3.432; 95% CI : 32.771-51.626; p=0.000). CONCLUSIONSIn this study, getting information about breastfeeding was the most influential factor of BSE in the early postpartum period. A woman's level of breastfeeding self-efficacy should be determined during the early postpartum period.